Knowledge management in organizations: a new proposal - Curado, Madalena (2010)
Organizations that display high levels of creativity and performance manage their knowledge effectively. Early Knowledge Management (KM) models tended to focus on explicit and quantifiable knowledge. Collectively, people in organizations display capabilities similar to those of human mind: accumulation of experience (memory), learning of new behaviors and understandings, and solving of problems and innovating (intelligence). Authors propose that these collective capabilities should be focused and managed. The paper describes a new approach to knowledge management, the Organizational Mind Model, a holistic approach that incorporates insights from three main streams of research in knowledge management: organizational memory, organizational learning and collective intelligence. Its application in an organizational setting illustrates the potentialities of the approach.